Penyelesaian Perselisihan Hubungan Industrial Menggunakan Acte Van Dading - Ari Yuliastuti; Emi Syarif (Pusat Penelitian dan Pengembangan Ketenagakerjaan Kementerian Ketenagakerjaan Republik Indonesia, 2021)
The industrial relations dispute settlement according to Act Number 2 Year 2004 Concerning Industrial Relations Dispute Settlement is divided into two manners. The first is out court dispute settlementt and the second is in court dispute settlement. The out court dispute settlement uses deliberation approach while the in court dispute settlement uses legal approach. The in court dispute settlement must be carried out after the out court dispute settlement is failure to make agreement. The Act Number 2 Year 2004 does not oversee the in court dispute settlemen through deliberation. The objective of this research is to get solution if the employee and the employer still want to settle the dispute through deliberation when the process has been in court. This research uses thenormative law research method and uses secondary law materials. The result of this research showed that the employee and the the employer could settle the dispute through deliberation eventhough the dispute has been in court if in this deliberation the parties could make agreement then this agreement must be made in peace agreement contract (Acte Van dading). The conclusion of this research is the employee and the the employer could still settle the dispute through deliberation eventhough the dispute has been in court.